PENGARUH KOMPLEKSITAS AUDIT, PROFITABILITAS KLIEN, UKURAN PERUSAHAAN DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT FEE - Mudrika Alamsyah Hasan (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
This research is to analyze the effect of audit complexity, client’s profitability, firmsize and audit firm size to audit fee in manufacturing companies listed on IndonesiaStock Exchange from 2012-2015.This research used secondary data that is auditedfinancial report which can be accessible through the website of Indonesia StockExchange www.idx.co.id. The population for this research is 135 manufacturingcompanies. The sampling method is purposive sampling. Based on this method, 45companies are acquired as a sample, with 4 years of observation period. Thus, thesum of this research is 180 analysis unit. Then audit complexity, client’s profitability,firm size, audit firm size and audit fee are tested using multiple linear regressionanalysis using SPSS 21.0. Before being conducted the regression test, it isexamined by using the classical assumption tests.The results of this researchindicate that audit complexity, client’s profitability, firm size and audit firm size havea positive and significant effect on audit fee with 0,009, 0,003, 0,000, and 0,025. Theeffect of independent variables on the dependent variable is 56,3%.